Acoustic Radiation Force Impulse Imaging: A New Tool for the Diagnosis of Papillary Thyroid Microcarcinoma. (22nd June 2014) - Zhang, Yi-Feng; Liu, Chang; Xu, Hui-Xiong; Xu, Jun-Mei; Zhang, Jing; Guo, Le-Hang; Zheng, Shu-Guang; Liu, Lin-Na; Xu, Xiao-Hong
Abstract : Purpose . To evaluate the diagnostic performance of ARFI imaging in differentiating between benign and malignant thyroid nodules <1 cm. Materials and Methods . 173 pathologically proven thyroid nodules (77 benign, 96 malignant) in 157 patients were included in this study. Receiver-operating characteristic curve (ROC) analyses were performed to assess the diagnostic performance of conventional ultrasound (US) and ARFI imaging in papillary thyroid microcarcinoma (PTMC). The independent risk factors for predicting PTMC were evaluated. Results . The mean SWV value of benign and malignant thyroid nodules were 2.57 ± 0.79 m/s (range: 0.90–4.92 m/s) and 3.88 ± 2.24 m/s (range: 1.49–9.00 m/s) (P = 0.000 ). Az for VTI elastography score was higher than that for hypoechoic, absence of halo sign, and type III vascularity (P < 0.05 ). The optimal cut-offs for VTI elastography score and SWV were score 4 and 3.10 m/s. Gender, hypoechoic, taller than wide, VTI elastography score ≥ 4, and SWV > 3.10 m/s had been found to be independent risk factors for predicting PTMC. Conclusion . ARFI elastography can provide elasticity information of PTMC quantitatively (VTQ) and directly reflects the overall elastic properties (VTI). Gender, hypoechogenicity, taller than wide, VTI elastography score ≥ 4, and SWV > 3.10 m/s are independent risk factors for predicting PTMC. ARFI elastography seems to be a new tool for the diagnosis of PTMC.